2013
DOI: 10.1002/adma.201302719
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Free Directed Patterning of a Highly Ordered Liquid Crystalline Organic Semiconductor via Template‐Assisted Self‐Assembly for Organic Transistors

Abstract: Highly ordered organic semiconductor micropatterns of the liquid-crystalline small molecule 2,7-didecylbenzothienobenzothiophene (C10 -BTBT) are fabricated using a simple method based on template-assisted self-assembly (TASA). The liquid crystallinity of C10 -BTBT allows solvent-free fabrication of high-performance printed organic field-effect transistors (OFETs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 37 publications
(64 reference statements)
1
43
0
Order By: Relevance
“…It was reported that 2,7-didecyl [1]benzothieno [3,2-b] [1] benzothiophene (C 10 -BTBT) TFTs with an alumina/polyimide gate insulator exhibited a field-effect mobility of 1.42 cm 2 /V s and an on/off current ratio of $10 6 [14]. Quasi single-crystalline C 10 -BTBT TFTs with alkyl chain-grafted polyimide gate insulators exhibited a field-effect mobility of 1.74 cm 2 /V s and an on/off current ratio of $10 5 [15]. Remarkably, organic TFTs with polyimide gate insulators showed excellent device performances.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It was reported that 2,7-didecyl [1]benzothieno [3,2-b] [1] benzothiophene (C 10 -BTBT) TFTs with an alumina/polyimide gate insulator exhibited a field-effect mobility of 1.42 cm 2 /V s and an on/off current ratio of $10 6 [14]. Quasi single-crystalline C 10 -BTBT TFTs with alkyl chain-grafted polyimide gate insulators exhibited a field-effect mobility of 1.74 cm 2 /V s and an on/off current ratio of $10 5 [15]. Remarkably, organic TFTs with polyimide gate insulators showed excellent device performances.…”
Section: Introductionmentioning
confidence: 98%
“…A variety of organic semiconductors for high-performance TFTs have been reported, while the development of organic gate insulators has been more limited. Recently, we reported the fabrication of polyimide gate insulators for high-performance organic TFTs [11][12][13][14][15]. Polyimide thin films have excellent electrical insulating properties.…”
Section: Introductionmentioning
confidence: 99%
“…UCL-001 exhibits liquid crystal phase (N phase) in the temperature range from 41 o C to the room temperature. The organic semiconductor material was C8-BTBT (Sigma-Aldrich) [7], which exhibits liquid crystal phase (SmA phase) in the temperature range from 123.7 to 103. …”
Section: Methodsmentioning
confidence: 99%
“…First, the device yield and reproducibility could be effectively improved based on the highly aligned organic crystal arrays. Second, crosstalk among devices as well as fluctuation of device performance could be remarkably reduced with the use of precisely patterned organic crystals . In the light of this, an efficient method is much desired to produce precisely patterned organic p–n heterojunction micro/nanocrystal arrays for high‐performance ambipolar OFETs.…”
Section: Surface Energies Of Photoresist (Su‐8) and Dif‐tes‐adt Determentioning
confidence: 99%